The accuracy of recognition of modified face elements of women and men - Vanagaitė, Kristina; Valickas, Gintautas; Soloveičikienė, Laura (Psichologija, 2005)
The article represents peculiarities of face elements recognition of different sexes. The goals of the research are: 1) to establish the accuracy and time of recognition of modified face elements and compare the results with the estimation of face typicality / distinctiveness; 2) to establish whether differences between sexes identifying modified face elements exist. With the help of computer-based photofit program there were target faces of two men and two women shaped. Research participants were supposed to memorize them. Replacing some particular elements of a target face (hair, eyes, lips and ears) with another ones there were new faces shaped. The research experts have selected five stimuli faces for the each target face. In the course of the research it was recorded whether the subjects (30 men and 30 women) noticed that the displayed faces differed from the target ones. While the created faces were being demonstrated the answers of the participants were registered with the help of the implemented computer program. In the end of the research, applying the 5 and 7 points scale, the participants assessed the easiness of recognition of face elements and the similarity among each other. Moreover, they indicated their strategy to identify modified elements of faces. The results showed that men as well as women were more accurate and fast in recognizing elements of modified faces of men, not those of women, which is statistically significant. A more accurate recognition of modified face elements might have been determined by a greater distinctiveness of target faces of men. Hair and eyes were recognized most accurately and quickly, after that proceeded lips and noses, while ears happened to be the most difficult elements to identify. The research also proved that the different speed and accuracy of recognition of modified face elements are connected: 1) with the strategy the participants applied (the correct answers were mostly presented applying a simultaneous recognition strategy); 2) with the subjective evaluation of the easiness of face elements recognition (the participants indicated most accurately those elements that were attributed to the easiest to recognize); 3) with the assessment of faces similarity (a higher level of perceived similarity of faces impedes the recognition of modified elements of a target face). Moreover, it was established that women in comparison with men are quicker and more accurate in recognizing modified elements of a target face.